Analisa Implementasi Tata Kelola Zakat Di Laz Sidogiri Cabang Bondowoso - Armawi Armawi (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
Zakat can function as a source of socio-economic funds for Muslims. This means that the utilization of zakat managed by the Amil Zakat Agency is not only limited to certain activities based on conventional orientation, but can also be used for the economic activities of the people, such as in poverty alleviation programs and unemployment by giving productive zakat to those who need it as business capital. The focus of the study in this research is as follows: 1. How is Zakat Management Planning in LAZ Sidogiri Bondowoso Branch?. 2. How is Zakat Management Organized at LAZ Sidogiri Bondowoso Branch?. 3. How is the Implementation of Zakat Management at LAZ Sidogiri Bondowoso Branch?. 4. How is Zakat Management Reporting at LAZ Sidogiri Bondowoso Branch? The results of this study indicate that the management of zakat carried out at LAZ Sidogiri includes Planning, Organizing, Distribution, and Reporting Zakat. 1) Planning for zakat management at LAZ Sidogiri Bondowoso branch is based on a plan that has been made nationally by the central LAZ Sidogiri in the annual work meeting, one of them is the centralization of the management of zakat funds systematically from the Bondowoso branch to the center. LAZ Sidogiri as the center for controlling the entire existing system, LAZ Sidogiri Bondowoso branch and other branches as implementers. 2) Organizing, LAZ Sidogiri to facilitate the task and run the wheels of the LAZ Bondowoso organization, is controlled by five implementers. The five people include: one branch head, one branch admin, and three funding officers. The recruitment model carried out by LAZ Bondowoso includes: first, LAZ Sidogiri proposes a new member candidate to the central LAZ Sidogiri, after that the central LAZ Sidogiri will approve or not. 3) Implementation, distribution of zakat funds, in the field shows that LAZ Sidogiri Bondowoso branch cannot immediately disburse funds and give them to mustahik, but must first confirm and submit disbursement. This is because LAZ Sidogiri Branch Bondowoso collects zakat funds, and the zakat funds are deposited to the central LAZ Sidogiri as a whole, as a form of centralization of funds. 4) Reporting on zakat collection at LAZ Sidogiri, Bondowoso branch absolutely uses the concept of Vertical Accountability, which is only responsible for all reporting to the central LAZ Sidogiri. This is because LAZ Sidogiri Bondowoso is legally parented to LAZ Sidogiri center in Pasuruan